Optimization of lime and clay-based hemp-concrete wall formulations for a successful lime rendering. (30th September 2018) - Arizzi, A.; Brümmer, M.; Martín-Sánchez, I.; Molina, E.; Cultrone, G.
Highlights: Drying time of compacted-hemp concrete blocks is increased by the presence of clay. 2-weeks-rendered blocks show more intense pigmentation and microbial colonization. Lime putty maintains higher RH underneath the render than natural hydraulic one. Aragonite on lime putty render is an evidence of the higher RH and organic content. Abstract: Different pathologies may arise on a wall finish if this is applied on a hemp-based rammed wall that is not completely dry. By simulating uneven drying and early-rendering of load-bearing and non-load-bearing hemp concrete blocks (made with natural hydraulic lime only or a mix of lime with clay) and studying them by means of chromatic, microbiological, textural and morphological investigations, we found that: it is advisable to wait at least ten weeks before rendering; adding clay to hemp concrete delays drying, leading to more intense deterioration of the render; natural hydraulic lime is the preferred binder for rendering hemp concrete.